Takotsubo’s Cardiomyopathy in a Patient with Kartagener’s Syndrome - Luis W. Dominguez; Robert P. Doggette; Fernando Gonzalez-Ibarra; Imam H. Shaik; Amer K. Syed (Case Reports in Medicine)
A 46-year-old African-American male with past medical history significant for Kartagener’s syndrome, essential hypertension, and HIV presented with acute chest pain. ECG and troponins indicated an acute myocardial infarction. Ventriculography confirmed dyskinesia of the left ventricle, with an EF of 25%. However the coronary catheterization showed nonobstructed coronaries. Ventricular contraction and EF were restored in 4 weeks. To our knowledge, this is the first incidence of Takotsubo’s reported in a young patient with Kartagener’s syndrome. Chronic lung disease may contribute to the development of Takotsubo’s cardiomyopathy, which is a documented yet not fully understood phenomenon.